Students’ Perception on the Use of Video Conferencing Software for Learning during the COVID-19 Pandemic - Saiful Akmal; Safrul Muluk; Habiburrahim Habiburrahim; Khairul Azmi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2022)
This study analyzes how students perceive the use of video conferencing software for educational purposes during the epidemic. During a pandemic, the researcher focuses on the students' use of Zoom, Google Meet, and Skype. This study's samples consist of six UIN Ar-Raniry English Language Department students with the online learning experience. This qualitative research collects data through interviews using purposive sampling. Several positive responses revealed that video conferencing software offers numerous advantages during the pandemic. Utilizing Zoom, Google Meet, and Skype is the most effective method for applying online learning throughout the pandemic's hard conditions. However, challenges such as adaptability to technological use, technical difficulties, and lack of computer literacy are inevitable.